Incidents in the anastomoses colorectal with mechanical suture - Harretche, Martín; Ruso, Luis; Carriquiry, Luis; Fernández, Gonzalo; Berhouet, Horacio; Rodríguez, Gustavo; Geninazzi, Héctor; Valeur, Patrice (Cirugía del Uruguay, 1999)
The history of the attempts to manufacture of suture machines, from the creation by Hu / ti in 1908, until the formation of the Research Institute Scientific Apparatus and Instruments Moscow Surgicals in 1951, where Andrussov and Amosov conducted a series of instruments for linear sutures and circular. The works carried out in the United States (1965) by Ravitch and Sterichen modified the Russian instruments, fine-tuning details that allow to perform correctly these sutures